Dilemmas in the formation of student identity in offshore higher education: a case study in Hong Kong - Chapman, A.; Pyvis, David (Routledge Publishing, Taylor & Francis Group, 2006)
This paper explores the impact of the internationalization of higher education on the formation of student identity. It does so in the context of increasing developments in offshore education and the rapid emergence of the professional doctorate in Australia and overseas. Drawing on data from a larger qualitative study of student experiences of offshore education, the focus is on professional doctorate candidates located in Hong Kong. Identity is characterized by a series of dilemmas experienced by the students as they seek to become members of the academic community. These dilemmas centre on a range of inter‐related issues, including sense of belonging, educational goals, learning style preferences and relationships with supervisors.